2019
DOI: 10.1088/1361-6528/ab40dd
|View full text |Cite
|
Sign up to set email alerts
|

Sputtering control of Ag2O decoration configurations on ZnO nanorods and their surface arrangement effects on photodegradation ability toward methyl orange

Abstract: In this study, a combinational strategy for synthesizing ZnO nanorod arrays interlaced with Ag2O particles was proposed. Hydrothermally derived ZnO nanorod templates were sputter coated with Ag2O particles. The sputtered Ag2O particles can be decorated on the surfaces of the ZnO nanorod arrays with a randomly dispersive or continuous coverage characteristic by controlling the sputtering duration. Structural analysis revealed the formation of satisfactory crystalline ZnO–Ag2O composite nanorods through the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The comparison of interface charge separation efficiency for various ZnO sheets was further investigated by the Nyquist plots with and without irradiation in Figure 7 c. The radius of the arc on the Nyquist plots reflects the interface layer resistance occurring at the surface of electrode. The smaller arc radius implies higher efficiency of the charge transfer ability [ 40 , 41 ]. The results in Figure 7 c showed that the decreasing order of the semicircular radius of the ZnO sheets with formation of a porous structure by conducting thermal annealing procedures.…”
Section: Resultsmentioning
confidence: 99%
“…The comparison of interface charge separation efficiency for various ZnO sheets was further investigated by the Nyquist plots with and without irradiation in Figure 7 c. The radius of the arc on the Nyquist plots reflects the interface layer resistance occurring at the surface of electrode. The smaller arc radius implies higher efficiency of the charge transfer ability [ 40 , 41 ]. The results in Figure 7 c showed that the decreasing order of the semicircular radius of the ZnO sheets with formation of a porous structure by conducting thermal annealing procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Silver oxide nanoparticles (SONPs) have been widely studied due to their unique optoelectronic property and high antibacterial activities. As a semiconducting material, SONPs are known to have a wide band-gap from 1.3 to 2.4 eV [1][2][3], making them suitable for photocatalytic applications, especially with the visible light-harvesting ability [4][5][6][7][8]. The SONP itself is utilized in photoelectrochemical or photocatalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the photoexcited electron-hole pairs were separated more effectively by the p-n junction formed in the TiO 2 -NiO composites than that formed in the pristine TiO 2 . This enabled the formation of more free carriers on the active sides of the composites and increased the photodegradation activity of the composites [31]. In addition, the NPT showed a higher degree of photodegradation than that of the NST.…”
Section: Resultsmentioning
confidence: 97%